Promoting Creators Intentions: Measurement Of Crowdfunding Performance - Wahjono, Sentot Imam; Fam, Soo Fen; Pakkanna, Mukhaer; Rasulong, Ismail; Anna Marina (Universiti Malaysia Sarawak, 2021)
Crowdfunding is an activity to collect small amounts of funds from a large audience via the internet without involving a financing intermediary. This study aims to determine the effect of fundraising, product testing, relationship reliability, and awareness-raising on the performance of the crowdfunding platform as an alternative source of business or business funding. This research was conducted using a quantitative approach, where Google forms were distributed to 267 project proponents, owners, or administrators in ASEAN countries as a sample and 197 sets of questionnaires were returned with complete answers and further analyzed. The data analysis used includes descriptive analysis, Pearson correlation, and multiple linear regression analysis. The results of this study indicate that all independent variables, namely the creator's intention in the form of fundraising, product testing, relationship reliability, and awareness-raising, have a positive and significant influence on the performance of the crowdfunding platform. This has practical implications that the creator's intention must be a concern for project proponents and fund owners who invest or distribute their funds in addition to paying attention to the business proposal and the reliability of the crowdfunding platform operator.